3D virtual histology of human pancreatic tissue by multiscale phase‐contrast X‐ray tomography. (26th October 2020) - Frohn, Jasper; Pinkert-Leetsch, Diana; Missbach-Güntner, Jeannine; Reichardt, Marius; Osterhoff, Markus; Alves, Frauke; Salditt, Tim
Abstract : This paper presents propagation‐based phase‐contrast tomography in two configurations at the beamline endstation GINIX, demonstrated on the application of 1 mm human pancreatic tumor tissue biopsies. Abstract : A multiscale three‐dimensional (3D) virtual histology approach is presented, based on two configurations of propagation phase‐contrast X‐ray tomography, which have been implemented in close proximity at the GINIX endstation at the beamline P10/PETRA III (DESY, Hamburg, Germany). This enables the 3D reconstruction of characteristic morphological features of human pancreatic normal and tumor tissue, as obtained from cancer surgery, first in the form of a large‐scale overview by parallel‐beam illumination, followed by a zoom into a region‐of‐interest based on zoom tomography using a Kirkpatrick–Baez mirror with additional waveguide optics. To this end 1 mm punch biopsies of the tissue were taken. In the parallel tomography, a volumetric throughput on the order of 0.01 mm 3 s −1 was achieved, while maintaining the ability to segment isolated cells. With a continuous rotation during the scan, a total acquisition time of less than 2 min was required for a full tomographic scan. Using the combination of both setups, islets of Langerhans, a three‐dimensional cluster of cells in the endocrine part of the pancreas, could be located. Cells in such an islet were segmented and visualized in 3D. Further, morphological alterations of tumorous tissue of the pancreas were characterized. To this end, the anisotropy parameter Ω, based on intensity gradients, was used in order to quantify the presence of collagen fibers within the entire biopsy specimen. This proof‐of‐concept experiment of the multiscale approach on human pancreatic tissue paves the way for future 3D virtual pathology.